2018
DOI: 10.3390/ma11091676
|View full text |Cite
|
Sign up to set email alerts
|

Control of Biofilm Formation in Healthcare: Recent Advances Exploiting Quorum-Sensing Interference Strategies and Multidrug Efflux Pump Inhibitors

Abstract: Biofilm formation in healthcare is an issue of considerable concern, as it results in increased morbidity and mortality, imposing a significant financial burden on the healthcare system. Biofilms are highly resistant to conventional antimicrobial therapies and lead to persistent infections. Hence, there is a high demand for novel strategies other than conventional antibiotic therapies to control biofilm-based infections. There are two approaches which have been employed so far to control biofilm formation in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 192 publications
(210 reference statements)
0
48
0
Order By: Relevance
“…EPIs could, therefore, play a major role in combating this global issue by reversing pathogenic resistance to the antibiotics. Studies have reported the ability of EPIs to reduce in vitro biofilm formation [92], which is one of the major contributing factors leading to phenotypic resistance/tolerance and multi-drug resistance. Their ability to directly affect biofilm formation and indirectly improve antibiotic activity makes them an attractive approach.…”
Section: Future Prospective and Conclusionmentioning
confidence: 99%
“…EPIs could, therefore, play a major role in combating this global issue by reversing pathogenic resistance to the antibiotics. Studies have reported the ability of EPIs to reduce in vitro biofilm formation [92], which is one of the major contributing factors leading to phenotypic resistance/tolerance and multi-drug resistance. Their ability to directly affect biofilm formation and indirectly improve antibiotic activity makes them an attractive approach.…”
Section: Future Prospective and Conclusionmentioning
confidence: 99%
“…Among them, the antibiotic efflux category appears the most dissimilar in comparison with all the categories analyzed. Multidrug efflux pumps received special attention in the past years due to their potential association with clinical multidrug resistance 83 Furthermore, recent advances demonstrate an important role of multidrug efflux pumps with biofilm formation, both mechanisms regulated by quorum-sensing mechanisms 84 . Since multidrug-resistant bacteria and biofilms have been the main targets in phage therapy 85,86 , these findings can reinforce the importance of phage study for more efficient control of S. aureus in mastitis.…”
Section: General Features Of S Aureus 3059 and Ufv2030rh1 Genomes Amentioning
confidence: 99%
“…Biofilms are involved in several infectious diseases, both in humans and animals, and are present in a wide range of ecosystems, such as food industries, medical equipment, and natural environments [ 5 , 6 , 7 ]. In the marine environment, biofilms on submerged surfaces serve as reservoirs for pathogenic bacteria, from which they can disseminate [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the toxic substances used as antifouling agents can be harmful to the natural environment [ 12 ]. Alternative preventive and curative approaches are currently being developed to specifically target mechanisms involved in biofilm formation or biofilm tolerance towards antimicrobials [ 7 , 11 , 13 ]. For example, enzymes inhibiting biofilm formation and disrupting pre-existing biofilms were shown to directly target the components of biofilm matrix by degrading the EPS [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%